Keterbatasan Pemuda dalam Menghadapi Dilema Standarisasi Perekrutan Tenaga Kerja : Studi Kasus : Job Fair yang Diadakan Disnaker di Bekasi - Robby Khairul Imam; Adil Fihukmi Farqi; Ovie Faiz Pratama; Anakku Saviola (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study discusses the limitations faced by young people in facing the dilemma of standardization of labor recruitment, with a case study on the implementation of the Job Fair held by the Manpower Office (Disnaker) in Bekasi. In an era of an increasingly competitive labor market, the recruitment process tends to refer to certain formal standards that do not always reflect the real potential of young job seekers, especially those from lower-middle economic backgrounds. This study uses a descriptive qualitative approach with data collection techniques through field observations, in-depth interviews with job fair participants, and documentation of materials and selection mechanisms used by companies. The results of the study indicate that many young people experience obstacles in meeting administrative and technical standards, such as expertise certification, work experience, and foreign language-based communication skills, which are now dominant requirements in labor selection. The gap between the actual abilities of young people and the demands of the labor market indicates hidden social exclusion in the recruitment system. These findings also highlight the minimal role of the state in equipping young people with skills that are in accordance with industry needs. This study recommends that the government not only facilitate recruitment through job fairs, but also be active in building a vocational training system based on local needs and reformulating a selection mechanism that is more inclusive and fair for all levels of youth.